Spatiotemporal evolution and driving factors of the rural settlements in the mountain-plain transitional zones - Sun, Daoliang; Hong, Buting; Ren, Ping (International Journal of Agricultural and Biological Engineering, 2022)
Identifying the spatiotemporal evolution characteristics of rural settlements and their driving factors is of great significance to layout optimization of rural settlements, intensive and economical use of rural land, and preparation of land space planning. Focusing on the mountain–plain transitional zone of Dujiangyan City, China, as the study area, this paper employs methods including landscape pattern index, kernel density estimation, average nearest neighbor index, and Geodetector to quantitatively analyze the spatiotemporal layout evolution characteristics of rural settlements and relevant driving factors in Dujiangyan City over the last decade. The four main findings are as follows. First, land use area of rural settlements and the quantity of patches in Dujiangyan exhibited synchronous changes during 2005-2015. Total class area (CA) increased from 6161.43 to 7265.43 hm2, then declined to 7043.01 hm2, and the number of patches (NP) increased from 16 543 to 26 018, and then declined to 25 890. Second, the maximum kernel density estimation values in the east and southeast of Dujiangyan City increased remarkably from 48.34 to 74.69 per hm2 during 2005-2010. Third, the average nearest neighbor index of rural settlements continually decreased in the foregoing 10 years, indicating a higher concentration of rural settlements. Finally, production and living conditions are the main driving factors of dynamic change in land use in rural settlements, while the impact of socio-economic factors is relatively smaller. Among others, the p-value of road accessibility is 0.057, and the impact p-value of land slope is 0.035.Keywords: rural settlement, spatiotemporal evolution, driving factors, geodetectorDOI: 10.25165/j.ijabe.20221502.5776Citation: Sun D L, Hong B T, Ren P. Spatiotemporal evolution and driving factors of the rural settlements in the mountain-plain transitional zones. Int J Agric & Biol Eng, 2022; 15(2): 149–155.